Functionalized silanes and electrolyte compositions and electrochemical devices containing them
Patent Information
- Application Number
- JP2024213109
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2014-10-03
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-21
Smart Images

Figure 2025026569000001_ABST
Abstract
Description
[Background technology]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 62 / 059,663, filed October 3, 2014, which is incorporated herein by reference.
[0002] The liquid electrolyte in lithium-ion batteries has traditionally been a lithium salt, usually LiPF 6 ) in an organic solvent blend of ethylene carbonate (EC) and one or more co-solvents, such as dimethyl carbonate (DMC), diethyl carbonate (DEC), or ethyl methyl carbonate (EMC). Unfortunately, LiPF 6 are unstable in these carbonate solvents above 60°C and at charging voltages above 4.3 volts. Use of lithium-ion batteries above these temperatures or voltages results in rapid degradation of electrode materials and battery performance. In addition, current lithium-ion electrolyte solvents have flash points around 35°C, which are the primary source of energy released during extreme failure of lithium-ion cells. Given these significant limitations, current electrolytes are hindering the development of advanced lithium-ion batteries for all applications, including portable products, electric drive vehicles (EDVs), and utility-scale applications. Dramatic reductions in battery failure rates are also required to effectively serve large lithium-ion batteries in EDV and grid-scale electricity storage applications.
[0003] Thus, there is a long unmet need for improved electrolyte solutions in energy storage devices, such as lithium ion batteries. Summary of the Invention
[0004] Disclosed herein are organosilicon (OS) compounds for use as electrolyte solvents in electrochemical devices, among other applications.
[0005] In general, OS compounds are environmentally friendly, non-flammable and high temperature resistant materials. These characteristics make OS materials well suited for use as electrolyte solvents, binders and coatings in energy storage devices. OS-based electrolytes are compatible with all lithium (Li)-based electrochemical systems (i.e., Li-ion, Li-air), including primary and rechargeable batteries, and capacitors (i.e., super / ultracapacitors). The incorporation of OS-based electrolytes into lithium batteries requires limited changes in cell design, and these electrolytes can be integrated into production operations with existing manufacturing processes and equipment.
[0006] The OS compounds described herein can be used as liquid electrolyte solvents to replace carbonate-based solvent systems in traditional lithium-ion batteries. The OS-based solvents significantly improve the performance and abuse resistance of lithium-ion batteries, including improved thermal stability at high temperatures over longer life spans, improved safety due to increased electrolyte flash point, improved voltage stability allowing the use of high voltage cathode materials and achieving higher energy density, low battery failure rates consistent with the requirements for large lithium batteries used in EDV and grid electricity storage applications, and compatibility with materials currently used in lithium-ion batteries for ease of adoption in current designs. Electric double layer capacitor (EDLC) devices have also been demonstrated to function with OS-based electrolytes. The OS compounds described herein can be used in OS-based electrolyte blends to meet the requirements of specific applications in industrial, military, and consumer product devices.
[0007] The objects and advantages of the compounds and electrolyte formulations of the present invention will become more fully apparent from the following detailed description and the accompanying drawings.
[0008] Thus, disclosed herein is the following. 1. [ka] is selected from the group consisting of "a" is an integer from 1 to 4, and "b" is an integer from 0 to (3×a); "Z" does not exist when "b" = 0, and "R" and [ka] is selected from the group consisting of Each "R" is independently halogen, C 1-6 Linear or branched alkyl, alkenyl or alkynyl and C 1-6 selected from the group consisting of linear or branched halo-alkyl, halo-alkenyl, or halo-alkynyl; Each "Sp" in formula I and II is independently C 1-15 Linear or branched alkylenyl and C 1-15 linear or branched halo-alkylenyl; Each "Y" in formula I is independently a compound selected from the group consisting of organic polar groups.
[0009] 2. Each "Y" is independent [ka] and the curved bond is selected from the group consisting of C 2-6 2. The compound of claim 1, exhibiting an akylene bridging moiety.
[0010] 3. Each "Y" is independent [ka] 3. The compound of claim 2, wherein the organic polar group is selected from the group consisting of:
[0011] 4. Each "R" is independently fluorine and C 1-6 selected from the group consisting of linear or branched fluoro-alkyl, fluoro-alkenyl or fluoro-alkynyl; Each "Sp" in formula I and II is independently C 1-15 4. The compound of claim 3, selected from the group consisting of linear or branched fluoro-alkylenyl.
[0012] 5. The compound according to any one of claims 1 to 4, wherein "a" is 1 and "b" is 0 to 3.
[0013] 6. The compound of claim 5, wherein "b" is 1 and "Z" is "-R".
[0014] 7. At least one "R" is fluorine and each "Sp" is independently C 1-6 Linear alkylene and C 1-6 6. The compound of claim 5, wherein the compound is selected from the group consisting of linear fluoro-alkylenes.
[0015] 8. The compound according to any one of claims 1 to 4, wherein "a" is 2 and "b" is 0 to 6.
[0016] 9. The compound of claim 7, wherein "b" is 1 and "Z" is "R".
[0017] 10. At least one "R" is fluorine and each "Sp" is independently C 1-6 8. The compound of claim 7, wherein said alkylene is selected from the group consisting of straight chain alkylene.
[0018] 11. The compound according to any one of claims 1 to 4, wherein "a" is 3 and "b" is 0 to 9.
[0019] 12. The compound of claim 11, wherein "b" is 1 and "Z" is "R".
[0020] 13. At least one "R" is fluorine and each "Sp" is independently C 1-6 12. The compound of claim 11, wherein the alkyl group is selected from the group consisting of straight chain alkylene.
[0021] 14. The compound according to any one of claims 1 to 4, wherein "a" is 4 and "b" is 0 to 12.
[0022] 15. The compound of claim 14, wherein "b" is 1 and "Z" is "R".
[0023] 16. At least one "R" is fluorine and each "Sp" is independently C 1-6 15. The compound of claim 14, wherein said alkylene is selected from the group consisting of straight chain alkylene.
[0024] 17. The compound according to any one of claims 1 to 4, wherein at least one "R" is fluorine.
[0025] 18. An electrolyte composition comprising a compound according to any one of claims 1 to 4 in combination with a salt.
[0026] 19. The electrolyte composition of claim 18, wherein the salt is a lithium-containing salt.
[0027] 20. An electrochemical device comprising the electrolyte composition of claim 18.
[0028] In more restrictive versions of the compounds of the invention, each "Y" is independently [ka] is an organic polar group selected from the group consisting of:
[0029] In addition, each "Y" is optional and independently [ka] The polar organic group may be selected from the group consisting of:
[0030] In an alternative version of the compound of the invention, "a" is 1, "b" is 0-2, and optionally "b" is 1 and "Z" is R. In this version, an optional embodiment includes at least one "R" being fluorine, and each "Sp" is independently a C which may be fluorinated. 1-6 It is selected from the group consisting of straight chain or branched alkylene.
[0031] In another alternative version of the compound of the invention, "a" is 2, "b" is 0-6, and optionally "b" is 1 and "Z" is R. In this version, an optional embodiment includes at least one "R" being fluorine and each "Sp" is independently a C which may be fluorinated. 1-6 It is selected from the group consisting of straight chain or branched alkylene.
[0032] In yet another alternative version of the compound of the invention, "a" is 3, "b" is 0-9, and optionally "b" is 1 and "Z" is R. In this version, any embodiment includes at least one "R" being fluorine and each "Sp" is independently a C which may be fluorinated. 1-6 It is selected from the group consisting of straight chain or branched alkylene.
[0033] In yet another alternative version of the compound of the invention, "a" is 4, "b" is 0-12, and optionally "b" is 1 and "Z" is R. In this version, any embodiment includes at least one "R" being fluorine and each "Sp" is independently a C which may be fluorinated. 1-6 It is selected from the group consisting of straight chain or branched alkylene.
[0034] Also disclosed herein is an electrolyte composition comprising a compound described herein in combination with a salt, preferably a lithium-containing salt. Also disclosed herein is an electrochemical device comprising the electrolyte composition.
[0035] By the nature of the subscripts "a" and "b," the following generic structures are clearly within the scope of the compounds disclosed and claimed herein. [ka] The various R groups are as defined above for "R", Sp is as defined above, and Y is as defined above. Preferably, in all versions of the compounds of the invention, Y is Li + It is an organic polar group that can coordinate to
[0036] When the polar group Y has a valence of 2 or more, the group has more than one substitution site. Thus, Y may have more than one silicon atom attached via a spacer group, as described above for the definition of Z. Thus, the following structures are also expressly within the scope of the compounds disclosed and claimed herein: [ka] etc.
[0037] In all versions of the compounds of the present invention, "halogen" includes fluoro, chloro, bromo, and iodo. Fluoro and chloro are preferred halogen substituents. The term "salt" is used herein in its conventional chemical sense to mean an ionic compound resulting from the neutralization reaction of an acid and a base. For purposes herein, salt is broadly defined to include all salts, including, but not limited to, sodium salts, lithium salts, magnesium salts, borates, phosphates, and the like. Non-limiting examples include sodium hexafluorophosphate, sodium perchlorate, sodium bis-trifluoromethanesulfonimide, magnesium hexafluorophosphate, magnesium perchlorate, magnesium bis-trifluoromethanesulfonimide, magnesium tetrafluoroborate, magnesium trifluoromethylsulfonate, tetraethylammonium tetrafluoroborate (TEA-TFB), tetrabutylphosphonium tetrafluoroborate, tetrabutylphosphonium hexafluorophosphate, tetrabutylammonium tetrafluoroborate, tetraethylammonium hexafluorophosphate, tetraethylammonium perchlorate, and tetraethylammonium bistrifluoromethanesulfonimidate. The term "lithium-containing salt" explicitly includes, but is not limited to, LiClO 4 , LiBF 4 , LiAsF 6 , LiPF 6 , LiCF 3 SO 3 , Li(CF 3 SO2 ) 2 N, Li(CF 3 SO 2 ) 3 C, LiN(SO 2 C 2 F 5 ) 2 , lithium alkylfluorophosphates and lithium bis(chelato)borate.
[0038] Also disclosed herein is an electrolyte composition comprising one or more organosilicon compounds described in the previous paragraph.Also disclosed herein is an electrochemical device comprising such electrolyte composition.The compounds disclosed herein are very useful for formulating electrolytes for use in any kind of charge storage device (e.g., cell, battery, capacitor, etc.).
[0039] The organosilicon solvent molecules disclosed herein have remarkable and unexpected thermal stability compared to conventional carbonate solvents. 6 Even when formulated into electrolyte compositions containing lithium salts such as LiPF, the organosilicon solvents exhibit outstanding resistance to exposure to high temperatures and breakdown during operation. As shown in the Examples and Figures, several variations of the organosilicon solvent molecules disclosed herein exhibit excellent resistance to breakdown during exposure to high temperatures and breakdown during operation, even when formulated into electrolyte compositions containing lithium salts such as LiPF 6 These data demonstrate the inherent strength of silicon as an essential stabilizing element in organosilicon molecular design. Variations of the molecules disclosed herein include non-fluorinated, fluorinated, polyfluorinated, polyfunctional and alternative alkyl structures, as well as many different Li + Coordination functional groups include nitriles, carbonates, sulfones, and esters, among many others. After exposure to 175°C for 60 minutes, 1M LiPF in organosilicon solvents was determined by both gas-phase and liquid-phase decomposition as measured by EI-MS and NMR, respectively. 6 Breakdown of the electrolyte plus salt was determined, and no significant gas or liquid phase decomposition of the OS solvent was observed.
[0040] Numeric ranges in this specification are intended to include all numbers and subsets of numbers within the range, whether or not they are specifically disclosed. Furthermore, these numerical ranges are intended to support claims directed to any number or subset of numbers within the range. For example, a disclosure of 1-10 is intended to support ranges such as 2-8, 3-7, 1-9, 3.6-4.6, 3.5-9.9, etc.
[0041] All references to a singular feature or limitation of the invention include the corresponding plural feature or limitation, and vice versa, unless expressly stated otherwise or clearly implied to the contrary from the context of the reference. Unless expressly limited to the singular, the indefinite article "a" shall mean "at least one."
[0042] Unless expressly stated otherwise or unless the contrary is clearly implied from the context when referring to a combination, all combinations of method or process steps herein can be performed in any order. [Brief description of the drawings]
[0043] [Figure 1] Figure 1A shows the oxidation stability of F1S3MN+LiPF6, LiBF4 or LiTFSI in terms of current density (mA / cm2) versus voltage (V vs Li / Li+). Figure 1B shows a detailed view of the same data as Figure 1A. [Diagram 2] 2A and 2B show the reduction stability of F1S3MN+LiPF6, LiBF4, or LiTFSI measured in duplicate as current density (mA / cm2) versus voltage (V vs Li / Li+). [Diagram 3] Figure 3A shows the oxidation stability of LiPF6 with F1S3MN or F1S3M2+1M in terms of current density (mA / cm2) versus voltage (V vs Li / Li+). Figure 3B shows a detailed view of the same data as Figure 3A. [Figure 4] The reduction stability of LiPF6 with F1S3MN or F1S3M2+1M is shown in terms of current density (mA / cm2) versus voltage (V vs Li / Li+). [Diagram 5] Figures 5A and 5B show the thermal stability of F1S3MN+LiPF6, where Figure 5A is a detailed view of the same data as Figure 5B. [Figure 6] The thermal stability of F1S3M2+LiPF6 is shown. [Figure 7] The thermal stability of F1S3MN+LiTFSI is shown. [Figure 8] The thermal stability of F1S3MN+LiBF4 is shown. [Figure 9] 1 shows the thermal stability of pure F1S3MN. [Figure 10] The thermal stability of DF1S3MN+20% EC and VC / LiBOB is shown. [Figure 11] 1 shows the enhanced stability of the F1S3MN electrolyte compared to the carbonate control heated with a delithiated NCA cathode. [Figure 12] 1 shows the discharge capacity of cells containing various electrolyte solvents at various C-rates at 30° C. [Figure 13] 1 shows the structure of a test cell. [Figure 14] 12. Discharge capacity of cells containing the same electrolyte solvent as in FIG. 12 at various C-rates and 55° C. [Figure 15] The structure of an EDLC device is shown. [Figure 16] 1 shows the performance of an EDLC device containing DF1S2MN electrolyte + TEA-BF4. [Figure 17] 1 shows the performance of EDLC devices containing various electrolyte solvents plus TBP-PF6. [Figure 18] The oxidation stability of 1ND1N+1M LiPF6 or 1M LiTFSI is shown in terms of current density (mA / cm2) versus voltage (V vs Li / Li+). [Figure 19] The reduction stability of 1ND1N+1M LiPF6 or 1M LiTFSI is shown in terms of current density (mA / cm2) versus voltage (V vs Li / Li+). [Figure 20]Figures 20A and 20B show current density (mA / cm2) versus voltage (V vs Li / Li+) for 1ND1N and 1M LiPF6 or 1M LiTFSI cycled from 0 to 6 V and 6 to 0 V. Figure 20A shows the first cycle. Figure 20B shows the second cycle. [Figure 21] Figure 21A shows the oxidation stability of LiPF6 with F1S3MN or 1ND1N+1M in terms of current density (mA / cm2) versus voltage (V versus Li / Li+). Figure 21B shows a detailed view of the same data as Figure 21A. [Figure 22] Figure 22A shows the oxidation stability of LiTFSI with F1S3MN or 1ND1N+1M in terms of current density (mA / cm2) versus voltage (V versus Li / Li+). Figure 22B shows a detailed view of the same data as Figure 22A. [Diagram 23] 1 is a mass spectrum showing the thermal stability of pure 1ND1N. [Figure 24] 1 is a mass spectrum showing the thermal stability of 1ND1N+LiPF6. [Diagram 25] Fig. 25A is a detailed view of m / z 24 to 30 in the mass spectral profile of Fig. 24. Fig. 25B is a detailed view of m / z 49 to 55 in the mass spectral profile of Fig. 24. [Figure 26] The thermal stability of 1ND1N+LiTFSI, vinylene carbonate (VC), and lithium bis(oxalato)borate (LiBOB) is shown. [Figure 27] Shows the thermal stability of 1ND1N+LiBF4. [Figure 28] 1 shows the discharge capacity of cells containing different electrolytes at different C-rates. [Figure 29] The discharge capacity of cells containing various other electrolyte solvents is shown and compared between the 1st and 50th cycles. [Figure 30A] 1 shows the discharge capacity of cells containing 1ND1N-LiPF6 based electrolyte at various C-rates. [Figure 30B] 1 shows the discharge capacity of cells containing 1ND1N-LiTFSI based electrolyte at various C-rates. [Diagram 31]The 1H-NMR spectrum (in CDCl3) of 1ND1N with peak assignments is shown. [Diagram 32] 1H-NMR spectrum (in CDCl3) of F1S3MN with peak assignments is shown. [Diagram 33] 1H-NMR spectrum (in CDCl3) of DF1S2MN with peak assignments is shown. [Diagram 34] 1H-NMR spectrum (in CDCl3) of DF1S3MN with peak assignments is shown. [Diagram 35] 1H-NMR spectrum (in CDCl3) of F1S3cMN with peak assignments is shown. [Diagram 36] The 1H-NMR spectrum (in CDCl3) of 1S3MN with peak assignments is shown. [Figure 37] FIG. 1 shows the gas phase decomposition of LiPF6 for F1S3MC, F1S3cMN, and 1S3DN+1M after 60 minutes at 175° C. The figure shows that there is no significant gas phase decomposition up to 175° C. [Figure 38] FIG. 1 shows the gas phase decomposition of LiPF6 for DF1S2MN, TF1S2MN, and TF1S3MN+1M after 60 minutes at 175° C. The figure shows that there is no significant gas phase decomposition up to 175° C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0044] Throughout the specification, a number of shorthand abbreviations are used to more easily describe the various organosilicon compounds. The following conventions are used:
[0045] FnSnMN compounds have the general formula: [ka] R 1 , R 2 and R 3 are the same or different, and independently C 1 ~C 6 A linear or branched alkyl, alkenyl, alkynyl or halogen (preferably F), and the "spacer" is selected from the group consisting of C 1~C 6 Linear or branched alkylene (preferably C 1 ~C 6 linear divalent alkylene), and Y is a polar organic moiety as described above.
[0046] The compounds disclosed herein can be produced by a number of different routes. The general approaches that can be used to produce the compounds are as follows: [ka] R 1 , R 2 and R 3 The groups are as defined herein for R. 4 has the same definition as Y. "n" is a positive integer.
[0047] The compounds disclosed herein can also be produced by the following approach. [ka] Again, R 1 , R 2 and R 3 The groups are as defined herein for R. 4 has the same definition as Y.
[0048] The compounds disclosed herein may also be made by a number of specific routes, including the following reaction schemes. [ka] and [ka] and [ka] and [ka] and [ka] and [ka] (R 4 is as defined above for Y) and [ka] (R 4 is as defined above for Y) and [ka] (R 4 is as defined above for Y)
[0049] LiTFSI, bis(trifluoromethane)sulfonimide lithium salt (Sigma-Aldrich catalog number 449504), is a commercial product supplied by several international suppliers. [ka]
[0050] The elements and method steps described herein may be used in any combination, whether or not stated.
[0051] All combinations of method steps herein can be performed in any order unless expressly stated otherwise or unless the contrary is clearly implied from the context when referring to a combination.
[0052] As used herein, the singular forms include plural referents unless the context clearly dictates otherwise.
[0053] All patents, patent publications, and peer-reviewed publications (i.e., "references") cited herein are expressly incorporated by reference to the same extent as if each individual reference was specifically and individually indicated to be incorporated by reference. In the event of a conflict between the present disclosure and the incorporated references, the present disclosure controls.
[0054] It is understood that the compounds and compositions disclosed herein are not limited to the particular configurations and arrangements of parts shown and described herein, but also include such modified forms thereof as fall within the scope of the claims.
[0055] The compounds of the present disclosure are organosilicon compounds that share a common structural feature in the form of one or more terminal or internal polar organic substituents or moieties.In this specification, the terms "polar organic substituent" and "polar organic moiety" are used interchangeably.The terms expressly include, but are not limited to, the following functional groups: [ka] [ka]
[0056] Preferred compounds include those of the following structures: [ka] [ka]
[0057] All of the above structures are depicted with a terminal cyano group. This is for the sake of brevity only. Analogous compounds having internal and / or terminal polar moieties as described above in place of the cyano moiety are clearly within the scope of this disclosure. Similarly, halogenated compounds are depicted above as fluorinated compounds. Analogous compounds having other halogen substituents (chlorine, bromine and / or iodine) in place of the fluorine atom are clearly within the scope of this disclosure. For each compound listed, two alternative systematic names are given (the first name of each pair of names has a nitrile underlying core and the second name has a silane underlying core). In addition, each compound is given an abbreviated name, where DF = difluoro, TF = trifluoro, and "Sn" denotes an alkylene spacer between the silicon atom and the terminal cyanate, isocyanate or thiocyanate moiety, and "n" represents the number of carbon atoms in the spacer. The physical properties of selected organosilicon (OS) compounds are shown in Table 1.
[0058] The synthesis of similar sulfones is exemplified below: 3 MS and DF1S 3 This can be achieved using the synthesis of MS. It should be noted that other sulfones falling within the broader disclosure contained herein can be produced by the same route simply by changing the starting reagents accordingly.
[0059] The synthesis of 1NMS proceeded as follows: 2-(methylsulfonyl)ethanol was dissolved in 0.5 molar equivalents of hexamethyldisilazane and approximately 1% molar equivalents of Al(H) as catalyst. 2 PO 4 ) 3 The mixture was kept at about 80°C overnight and distilled twice to give pure 1NMS. [ka]
[0060] F1S 3 The synthesis of MS proceeded as follows: Allyl methyl sulfide was dissolved in ethanol and 4 molar equivalents of H 2 O2 Approximately 3% molar equivalent of ammonium heptamolybdate was added as a catalyst for the oxidation. The next day, the solution was diluted with NaHCO 3 Neutralize with solution and CH 2 Cl 2 The aqueous fraction was discarded, and the organic layer was evaporated and distilled to give allyl methyl sulfone. Allyl methyl sulfone was hydrosilylated with dimethylchlorosilane using Karstedt's catalyst. The product was fluorinated at about 150 °C using NaFHF, filtered, distilled twice, and dried over molecular sieves to give pure F1S. 3 MS was obtained. [ka] DF1S 3 The synthesis of MS proceeded as follows: 3-mercaptopropylmethyldimethoxysilane was dissolved in ethanol and mixed with 1 molar equivalent of NaOH in water. Then, 1 molar equivalent of Me 2 SO 4 The mixture was added and refluxed overnight. The solid was filtered off. The crude product was diluted with 4 molar equivalents of H 2 O 2 and 3% molar equivalents of ammonium heptamolybdate. The solvent was evaporated and 2 molar equivalents of HF in water were added. The product was separated into CH 2 Cl 2 Extracted and distilled. [ka]
[0061] Additional characterization data for these sulfone compounds is contained in the appendix attached hereto and incorporated by reference.
[0062] As shown in Table 1, the addition of fluorine and the shortening of the spacer length decreased the viscosity, increased the conductivity, and decreased the flash point. 2 MN has the lowest viscosity and highest conductivity.
[0063] [Table 1] key: [ka]
[0064] Pure 1ND2, 1ND1, 1ND1N, F1S 3 MN, DPF1S 3 MN, F1S 3 MC, F1S 3 ME, F1S 3 MA, F1S 3 MS, 1NMS, F1S 3 M2 and F1S 3c The physical properties of MN and the electrolyte solutions containing these solvents are shown in Table 2.
[0065] [Table 2] key: [ka]
[0066] In addition to the organosilicon compounds disclosed herein, the electrolyte compositions of the present invention may contain conventional non-silicon co-solvents. For example, the electrolyte compositions of the present invention may contain nitriles and carbonates, such as acetonitrile, ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC) or ethyl methyl carbonate (EMC). The electrolyte compositions may contain non-silicon co-solvents in a wide range of concentrations, including but not limited to about 1 to about 40% by weight. Examples of suitable co-solvent concentrations include about 1% by weight, about 5% by weight, about 10% by weight, about 15% by weight, about 20% by weight, about 25% by weight, about 30% by weight, about 40% by weight, or ranges between and including the foregoing amounts. EXAMPLES
[0067] F1S 3 MN synthesis: Scheme 1 is F1S 3The synthesis scheme of MN is shown below. [F] is a fluorinating agent such as HF, NH 4 FHF or other fluorinating agent. NH 4 FHF is preferably used as the fluorinating agent for laboratory scale synthesis. If HF is used, the only by-product is HCl. 3 The MN compound is washed from the solid salt with hexane, distilled, dried over CaO, and distilled again. [ka] Scheme 1
[0068] Scheme 2 shows NH as the fluorinating agent. 4 F1S using FHF 3 The synthesis scheme of MN is shown. Karstedt's catalyst (Platinum(0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex solution, catalog number 479519, Sigma-Aldrich, St. Louis, MO) was used to synthesize isoF1S, where approximately 3% substitution occurs at the secondary carbon. 3 MN is generated. This isof1S 3 MN is F1S 3 It has a lower boiling point than MN, and most of it can be separated by fractional distillation. [ka]
[0069] Scheme 3 shows Cl1S 3 F1S using MN intermediate 3 An alternative, shorter synthetic scheme for MN is shown. 3 MN intermediates can be obtained from Gelest, Inc. (product code SIC2452.0, 11 East Steele Road, Morrisville, PA). 3 The use of the MN intermediate shortens the synthesis time. [ka] Scheme 3
[0070] Scheme 4 is F1S 3 Another synthetic scheme for MN is shown below. As in Scheme 1, [F] is a fluorinating agent, e.g., HF, NH 4 FHF or other fluorinating agent is shown. The use of HF as the fluorinating agent in this synthesis scheme does not produce any solid by-products, so hexane extraction and filtration of solids are not necessary. The only by-product is HCl. [ka] Scheme 4
[0071] Scheme 5 is F1S 3 Another synthetic scheme for MN is shown below. As in Scheme 1, [F] is a fluorinating agent, e.g., HF, NH 4 FHF or other fluorinating agent. [ka]
[0072] F1S 3 Synthesis of MN: In the preferred route, allyl cyanide is heated to about 100°C with a small amount of Karstedt's catalyst. Dimethylchlorosilane is added dropwise and refluxed for 4 hours. After cooling to room temperature, the mixture is fluorinated using 1 molar equivalent of ammonium bifluoride at room temperature. Cold hexane is added to the mixture, the solids are filtered off, and the solvent is evaporated. Calcium oxide is added to the crude product and distillation under vacuum at 45-55°C and 0.4 Torr gives the desired product F1S. 3 MN was obtained.
[0073] F1S 3 Synthesis of ME: [ka] Scheme 6
[0074] In the preferred route, allyl acetate is mixed with dimethylchlorosilane and a small amount of Karstedt's catalyst is added. The mixture is allowed to react overnight. The following day, the mixture is fluorinated with 0.33 molar equivalents of antimony trifluoride at room temperature overnight with vigorous stirring. The following day, the solids are filtered off and the product is distilled under vacuum at 25-30°C and 0.3 Torr to give the desired product F1S. 3 ME was obtained.
[0075] The ester is suitable as an electrochemical solvent in an electrolyte composition. 3 ME is 1M LiPF 6 It has good solubility in lithium and dissolves rapidly at room temperature. Its flash point is acceptable at 66°C and its dielectric constant is similar at 6.6. Its CV oxidation / reduction behavior is also suitable for lithium-ion charge storage cells. It has an F1S of 80%. 3 Full cycling of the cell with ME electrolyte was stable and the capacity was good. Very low current density was maintained at 30°C with potentials below 5V. F1S 3 ME is electrochemically viable through the underlying Pt oxidation and graphite reduction. Normal reduction behavior was observed in the first cycle, and passivation was observed in the second cycle. Over 26 cycles, F1S 3 ME cycled well in an 80% electrolyte formulation in an NMC / graphite electrode system (data not shown).
[0076] DF1S 3 DN composition: [ka] Scheme 7
[0077] Bis(cyanopropyl)dichlorosilane was mixed with 2 molar equivalents of aqueous HF at room temperature and allowed to react overnight. The crude product was extracted with dichloromethane, the solvent was evaporated, and the product was distilled under vacuum at 165° C. and 0.1 Torr to give the desired product, DF1S. 3 DN was obtained.
[0078] 1S 3DN composition: [ka] Scheme 8
[0079] DF1S 3 DN was dissolved in THF and cooled in an ice bath, then 2 molar equivalents of methylmagnesium bromide were added and the mixture was allowed to react until it slowly reached room temperature. The mixture was quenched with ethanol, the crude product was extracted with dichloromethane, the solvent was evaporated, and the product was distilled under vacuum at 125 °C and 0.2 Torr to give the desired product 1S. 3 DN was obtained.
[0080] TF1S 3 Synthesis of MN: [ka] Scheme 9
[0081] Cyanopropyltrichlorosilane was cooled in an ice bath and 4 molar equivalents of aqueous HF was added dropwise. The mixture was allowed to react for up to 2 hours. The crude product was extracted with dichloromethane, the solvent was evaporated, and the product was distilled under vacuum at 25° C. and 0.2 Torr to give the desired product TF1S. 3 MN was obtained.
[0082] DPF1S 3 Synthesis of MN: [ka] Scheme 10
[0083] Bis(isopropyl)cyanopropylchlorosilane was dissolved in THF and cooled in an ice bath, then 1 molar equivalent of aqueous HF was added dropwise and allowed to react at room temperature overnight. The next day, the solvent was evaporated and the product was distilled under vacuum at 60° C. and 0.2 Torr to give the desired product DPF1S. 3 MN was obtained.
[0084] DPF1S 3By creating LiPF, we investigated how increasing the alkyl group on the silicon atom affects the physical and electronic properties of the molecule. 6 It has good solubility in ethylenediaminetetraacetate and dissolves rapidly at room temperature. It exhibits stable oxidation behavior in cyclic voltammetry (CV) up to about 5 V. Its CV reduction behavior is also good, with passivation occurring in the second cycle. This compound is suitable for electrochemical applications at high temperatures (flash point = 118°C) and potentials up to about 5 V. DPF1S 3 MN is electrochemically viable via the underlying Pt oxidation and graphite reduction.
[0085] DF1S 3 Synthesis of MSO: [ka] Scheme 11
[0086] DF1S 3 MSO follows the procedure described in DF1S 3 Obtained as a by-product of incomplete oxidation during the synthesis of MS. 3 MSO was purified by distillation under vacuum at 40° C. and 0.1 Torr.
[0087] F1S 3 Synthesis of MA: [ka] Scheme 12
[0088] In this synthesis, 2 molar equivalents of dimethylallylamine are mixed with 1,1,3,3-tetramethyldisiloxane and a small amount of Karstedt's catalyst. The mixture is heated to 100°C and allowed to react overnight. The following day, the mixture is fluorinated with 0.67 molar equivalents of antimony trifluoride at 150°C overnight with vigorous stirring. The following day, the solids are filtered off and the product is distilled under vacuum at 20-25°C and 0.2 Torr to give the desired product F1S. 3 MA was obtained.
[0089] F1S 3 Synthesis of MC: [ka] Scheme 13
[0090] Allyl alcohol was silylated with hexamethyldisilazane using catalytic amount of aluminum dihydrogen phosphate at 80° C. overnight. Before hydrosilylation, the intermediate allyloxytrimethylsilane was purified by distillation. Hydrosilylation was carried out overnight using 1 molar equivalent of dimethylchlorosilane and a small amount of Karstedt's catalyst at 80° C. The next day, the mixture was fluorinated and hydrolyzed with 2 molar equivalents of aqueous hydrofluoric acid at room temperature under vigorous stirring to give (3-hydroxypropyl)dimethylfluorosilane, which was distilled before the next step. The last intermediate was dissolved in hexane, 1 molar equivalent of trimethylamine was added, the mixture was cooled in an ice bath, methyl chloroformate was added dropwise to the mixture, and then reacted overnight at room temperature. The next day, the solids were filtered off, the solvent was evaporated, and the product was distilled under vacuum at 28° C. at 0.2 Torr to give the desired product F1S. 3 MC was obtained.
[0091] F1S 3 MC was synthesized and its electrochemical performance compared with that of commonly used carbonates and their silyl analogues. 3 The CV oxidation and reduction of MC proved to be suitable for electrochemical applications. The synthesis was very successful, and F1S 3 MC was obtained with a purity of >99.8%. F1S 3 MC is 1M LiPF 6 It dissolved rapidly at room temperature. It showed acceptable cycling at 30°C with good capacity. F1S 3 MC also showed good oxidative stability up to potentials of about 5 V. In the CV, reduction showed two peaks in the first cycle (1.7 V and 0.6 V), while passivation was observed in the second cycle.
[0092] Determining the electrochemical stability of organosilicon materials Computational chemistry methods were used to calculate the electrochemical properties of various organosilicon molecules. The inventors used the GAMESS program developed by the Gordon research team at Iowa State University for density functional theory (DFT) molecular orbital calculations. The HOMO (highest occupied molecular orbital) and LUMO (lowest unoccupied molecular orbital) energy levels (correlated with the reduction and oxidation potentials of the compounds) were calculated at the B3LYP / DZV level. The oxidation stability of electrolytes containing organosilicon solvents was measured in a three-electrode cell using linear sweep voltammetry (LSV) or cyclic voltammetry (CV). A platinum microelectrode was used as the working electrode and lithium metal as both the counter and reference electrodes. The potential of the system was measured from the open circuit voltage (OCV) to 6 or 8 V (vs. Li / Li + ) at a scan rate of 10 mV / s. The resulting current density (mA / cm 2 ) was recorded at each potential, with higher currents indicating oxidation reactions (i.e., lower oxidative stability). For linear sweep voltammetry, 8 V was used as the final potential to evaluate the basic oxidative stability of the materials over a wider voltage range. For cyclic voltammetry, 6 V was used to evaluate the materials over multiple scans at potentials more relevant to traditional battery applications. Multiple scans were performed in the cyclic voltammetry experiments to determine the reversibility / irreversibility of the observed reactions.
[0093] The reduction stability of electrolytes containing organosilicon solvents was measured in a three-electrode cell using linear sweep voltammetry (LSV). A glassy carbon electrode was used as the working electrode and lithium metal was used as both the counter and reference electrodes. The potential of the system was varied from the open circuit voltage (OCV, typically 3 V) to 0.1 V (vs. Li / Li + ) at a scan rate of 10 mV / s. The resulting current density (mA / cm 2 ) was recorded at each potential, with larger currents indicating a reduction reaction (i.e., lower reduction stability). Two scans were performed to assess whether the reduction process was reversible or irreversible (i.e., passivation occurred).
[0094] F1S 3Electrochemical stability of MN: F1S 3 MN and F1S 3 The molecular orbital diagram for M2 (not shown) shows that the energy difference between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) is F1S 3 MN (9.07 eV) is F1S 3 This indicates that the value is greater than M2 (8.20 eV). 3 MN is F1S 3 It also has a higher oxidation potential (-8.75 eV) than M2 (-6.84 eV).
[0095] Figures 1A and 1B show the F1S 3 MN+LiPF 6 , LiBF 4 The oxidation stability of LiTFSI was measured using a current density (mA / cm 2 ) vs. Voltage (V vs. Li / Li + The oxidation stability was measured at room temperature using a Pt working electrode, a Li counter electrode, and a Li / Li + The test was performed with a reference electrode of 100 μm and a sweep rate of 10 mV / s. Figure 1B shows a detailed view of the same data as in Figure 1A. 3 MN-LiPF 6 The electrolyte showed the best oxidation stability and a current density of 1mA / cm 2 at 7.3V, whereas F1S 3 MN-LiBF 4 and F1S 3 MN-LiTFSI has a current density of 1mA / cm 2 at 6.8V and 6.2V.
[0096] 2A and 2B show the F1S 3 MN+LiPF 6 , LiBF 4 The reduction stability of LiTFSI was evaluated using current density (mA / cm 2 ) vs. Voltage (V vs. Li / Li + The reduction stability was measured at room temperature using a Pt working electrode, a Li counter electrode, and a Li / Li + A reference electrode of 100 μm and a sweep rate of 10 mV / s were used. Figures 2A and 2B are two separate scans. 3 MN-LiPF 6The electrolyte showed the best reduction stability.
[0097] 3A and 3B are diagrams showing the F1S 3 MN or F1S 3 M2+1M LiPF 6 The oxidation stability of 2 ) vs. Voltage (V vs. Li / Li + The oxidation stability was measured at room temperature using a Pt working electrode, a Li counter electrode, and a Li / Li + The test was performed with a reference electrode of 100 μm and a sweep rate of 10 mV / s. Figure 3B shows a detailed view of the same data as in Figure 3A. 3 MN is F1S 3 It showed improved oxidative stability than M2.
[0098] Figure 4 shows the F1S 3 MN or F1S 3 M2+1M LiPF 6 The reduction stability of carbonate control electrolyte + LiPF 6 and current density (mA / cm 2 ) vs. Voltage (V vs. Li / Li + The reduction stability was compared at room temperature with a Pt working electrode, a Li counter electrode, and a Li / Li + The test was performed with a reference electrode of 1000 and a sweep rate of 10 mV / s. 3 MN is F1S 3 It showed lower reduction resistance than M2.
[0099] Measurement of the thermal stability of pure solvents and formulated electrolytes The thermal stability of both the pure organosilicon solvent and the electrolyte composition was measured as follows: Approximately 0.75 mL of liquid sample was heated in a sealed cell under an argon purge. The argon purge was continued to an air sampling mass spectrometer, where any gas phase impurities and / or decomposition products can be detected at very low levels using electron impact mass spectrometry (EI-MS). The sample was held at predefined temperature levels relevant for battery applications (30, 55, 70, 100, 125, 150, 175 and 200°C) for 1 hour. Gas phase decomposition products were identified by comparing the fragmentation patterns obtained by EI-MS with NIST standards. Following the heating experiment (and detection / recovery of all gas phase products), the remaining liquid sample was analyzed by NMR spectroscopy to quantitatively analyze the extent of decomposition. All components of the system, including the organosilicon solvent, carbonate co-solvent, all additives and lithium salt (if present), were fully analyzed using multiple nuclei probes.
[0100] F1S 3 Thermal stability of MN: 5A and 5B are schematic diagrams of the F1S 3 MN+LiPF 6 The thermal stability of F1S is shown. 3 MN-LiPF 6 The electrolyte (batch ZP815-01) was exposed to temperatures ranging from 30 to 175°C and analyzed for gaseous and liquid decomposition products by electron impact mass spectrometry (EI-MS) and nuclear magnetic resonance spectroscopy (NMR), respectively. The temperatures at which prominent peaks were observed are annotated. F1S 3 MN did not show any significant gas and / or liquid phase decomposition up to 175°C. 2 SiF 2 appears at 81 m / z at temperatures between 100 and 125°C, and MeSiF 3 appeared at 85 m / z at temperatures between 150 and 175°C. However, the 81 m / z and 85 m / z peaks appeared irregularly at temperatures between 100 and 175°C. Furthermore, 1 H NMR analysis showed no decomposition after heating to 175 °C. 3 MN does not show any consistent decomposition up to 175° C. Figure 5A shows a detailed view of the same data as Figure 5B.
[0101] Figure 6 shows the F1S 3 M2+LiPF 6 The thermal stability of F1S is shown. 3 M2-LiPF 6 The electrolyte was exposed to temperatures between 30 and 150°C and analyzed for decomposition products by mass spectrometry. The temperatures at which prominent peaks were observed are annotated. F1S 3 M2 showed decomposition at temperatures ≥ 125°C. The decomposition products were Me 2 SiF 2 and 1,4-dioxane. 1 H NMR analysis showed about 6% decomposition at 150 °C. These results, along with those discussed in connection with Figures 5A and 5B, indicate that F1S 3 MN is F1S 3 This indicates that it is more thermally stable than M2.
[0102] Figure 7 shows the F1S 3 Thermal stability of MN+LiTFSI. F1S 3 The MN-LiTFSI electrolyte was exposed to temperatures between 30 and 185°C and analyzed for decomposition products by mass spectrometry. The temperatures at which prominent peaks were observed are annotated. Gas phase peaks were observed at temperatures ≥ 150°C. The 117 and 102 peaks were from the F1S 3 MN-LiBF 4 This matched the patterns observed for the electrolyte and pure solvent (see Figures 8 and 9).
[0103] Figure 8 shows the F1S 3 MN+LiBF 4 The thermal stability of F1S is shown. 3 MN-LiBF 4 The electrolyte was exposed to temperatures between 30 and 200°C and analyzed for decomposition products by mass spectrometry. The temperatures at which prominent peaks were observed are annotated. Gas phase peaks were observed at temperatures ≥ 175°C. The 117 and 102 peaks were observed in pure solvent and F1S 3 This matched the pattern observed for the MN-LiTFSI electrolyte (see Figures 7 and 9). 1H NMR analysis showed the absence of fluorinated decomposition products and <0.5% non-fluorinated hydrolysis products.
[0104] Figure 9 shows a pure F1S 3 The thermal stability of MN is shown. F1S 3 The MN electrolyte was exposed to temperatures between 30 and 195°C and analyzed for decomposition products by mass spectrometry. The temperatures at which prominent peaks were observed are annotated. Gas phase peaks were observed at temperatures ≥ 150°C. At 150°C, Me 2 SiF 2 was observed (96 / 81 m / z), but no other peaks were associated with this product. 1 H NMR analysis showed the absence of fluorinated decomposition products and <0.5% hydrolysis.
[0105] The above data is from F1S 3 MN is LiPF 6 This indicates that it is the most thermally stable OS solvent.
[0106] DF1S 3 Synthesis of MN: [ka] Scheme 14
[0107] Commercially available 3-cyanopropyldichloromethylsilane (CAS number 1190-16-5, Sigma Aldrich, St. Louis, MO, USA) was fluorinated with ammonium bifluoride at room temperature. Cold hexane was then added to the mixture. The solids were filtered off and the solvent was evaporated. Calcium oxide was added to the crude product. The solvent was distilled under vacuum at 35-45 °C and 0.4 Torr to give the desired product in very high purity (about 99.8%) and about 90% yield.
[0108] DF1S 2 Synthesis of MN: [ka] Scheme 15
[0109] Acrylonitrile was mixed with N,N,N',N'-tetramethylethylenediamine and copper(I) oxide in a flask and heated to 60°C. Dichloromethylsilane was then added dropwise and refluxed overnight. After cooling to room temperature, the mixture was distilled under vacuum (43°C, 0.2 Torr) to give the dichloro intermediate (DC1S 2 MN) was obtained. This intermediate was fluorinated using 1.2 molar equivalents of ammonium bifluoride at room temperature or 1.2 molar equivalents of sodium bifluoride at 130°C. Dichloromethane was then added and the solid was filtered off. The solvent was evaporated and the crude product was distilled under vacuum. Triethylamine and molecular sieves were added to the product and distilled under vacuum at 25-33°C and 0.1 Torr to give the desired product in very high purity (>99%) and about 75% yield.
[0110] DF1S 3 Thermal stability of MN: Figure 10 shows the DF1S 3 MN+LiPF 6 The thermal stability of DF1S 3 MN-LiPF 6 The electrolyte (ZP990-01) was exposed to temperatures ranging from 30 to 150 °C and analyzed for gaseous and liquid decomposition products by electron impact mass spectrometry (EI-MS) and nuclear magnetic resonance spectroscopy (NMR), respectively. 3 MN did not show any significant gas and / or liquid phase decomposition up to 150 °C.
[0111] Differential Scanning Calorimetry (DSC) evaluation of resistance to thermal abuse: DSC measurement F1S 3 MN and carbonate-based electrolytes were performed in the presence of delithiated cathode materials to evaluate potential thermal abuse resistance effects that could translate into safety benefits in the complete cell configuration. Higher onset temperature, lower total heat output, and lower peak heat output are all effects suggestive of improved thermal abuse behavior in the complete cell configuration.
[0112] Figure 11 shows the F1S 3MN+LiPF 6 and thermal stability of various carbonate cosolvents, carbonate control electrolyte + LiPF 6 are compared. Cells containing each electrolyte were charged to 4.25 V and then disassembled. Lithium nickel cobalt aluminum oxide (NCA) cathodes were rinsed with diethylene carbonate and dried. Each sample, containing 5 mg of active material and 2 mg of fresh electrolyte, was sealed in a stainless steel DSC pan. DSC scans at a rate of 2°C / min showed that the carbonate control electrolyte reacted at a much lower onset temperature than any of the organosilicon electrolyte blends. In addition, the electrolytes in which EMC was replaced with organosilicon have a much lower peak heat output than the control electrolyte.
[0113] Preparation of electrolyte Blending of the electrolyte is completed in a moisture-free (<5 ppm) and oxygen-free (<20 ppm) argon glovebox. All electrolyte components including solvents, salts, and additives are properly dried prior to blending and stored in the glovebox. Solvent moisture is monitored periodically with Karl Fischer measurements to maintain moisture levels at <20 ppm. In general, the solvent is first weighed into a separate vial and mixed until homogeneous. 70% of the solvent is placed in a volumetric flask. The lithium (or other) salt is slowly added and stirred with a magnetic stir bar until completely dissolved. Next, the other additives (i.e., VC, LiBOB) are slowly added and stirred until the solution is homogeneous. Remove the stir bar and add some of the remaining solvent to complete the volume requirement. Place the stir bar back in the volumetric flask and stir the electrolyte until homogeneous. After blending is complete, the electrolyte is placed in a dry vial or alternative container for storage.
[0114] F1S 3 Performance in MN Li-ion cells: FIG. 12 shows the discharge capacity at 30° C. of cells containing various electrolyte solvents. Three different electrolyte solvents were tested in lithium ion cells over a series of cycles at various C-rates in a 2032 size coin cell assembly (stacked assembly as shown in FIG. 13). The assembly includes a graphite anode, a lithium nickel cobalt aluminum oxide (NCA) cathode, and a "2500" type separator from Celgard, LLC (Charlotte, NC). The three electrolyte solvents were (1) a control EPA6 carbonate electrolyte (triangles) containing ethylene carbonate (EC) and diethyl carbonate (DEC) on a 1:1 volumetric basis; (2) a 79% F1S 3 MN, 20% EC, 1M LiPF 6 and F1S containing solid electrolyte interphase (SEI) forming additives 3 MN-based electrolyte (square) and (3) 79% F1S 3 M2, 20% EC, 1M LiPF 6 and F1S containing SEI forming additives 3 M2-based electrolyte (circle). As shown in Figure 12, F1S 3 MN-based electrolytes are equivalent to EPA6 at 4C rates.
[0115] FIG. 14 shows the discharge capacity at 55° C. of cells containing the same electrolyte as shown and described in FIG. 12. The cells were assembled in the same manner and cycled at a C / 2 rate. As shown in FIG. 3 MN solvents were run at 55°C, with carbonate controls and F1S 3 Both M2-based electrolytes had improved cycling stability.
[0116] F1S in electric double layer capacitor cells 3 MN and DF1S 2 MN performance: A symmetric electric double-layer capacitor (EDLC) was assembled in a CR2032 coin cell as shown in Figure 15. A glass fiber separator (AP40, Merck Millipore) was sandwiched between two AC cross electrodes, and 100 μL of electrolyte was added to the separator. Tetraethylammonium tetrafluoroborate (TEA-BF 4 , Alfa Aesar, 99%) and tetrabutylphosphonium hexafluorophosphate (TBP-PF 6 , Sigma Aldrich, ≥99.0%) was used as salt. 3 MN(99.4%) and DF1S 2 Organosilicon solvent MN (99.8%) was manufactured by Silatronix. Acetonitrile (AN, Sigma Aldrich, anhydrous, 99.8%) was used as a co-solvent.
[0117] Zorflex FM10 100% activated carbon (AC) cloth from Calgon carbon was used for both electrodes. FM10 has a surface area of 1000–2000 m 2 / g, thickness 0.5mm and areal density 120g / m 2 The AC cloth was punched into disks with a diameter of 15 mm and used directly as electrodes without any binder or conductive additives.
[0118] The performance of the EDLC cell was tested by cyclic voltammetry (CV) using a Biologic BMP300 potentiostat. Temperature variations in the furnace were controlled at ±0.1°C. The cyclic voltammetry (CV) response of the EDLC cell was taken from 0 to 3 V at a scan rate of 10 mV / s. The normalized specific capacitance, C, was calculated using the following equation [1,2]:
number
[0119] Figure 16 shows the TEA-BF 4Figure 1 shows the cyclic voltammograms of an EDLC cell with OS electrolyte containing salt. The electrolyte ZX1193 is 70 volume percent DF1S. 2 MN and 1.0 M TEA-BF dissolved in 30 volume percent acetonitrile 4 The electrolyte ZX1190 was a 60:40 blend of DF1S by volume. 2 MN and 0.8M TEA-BF dissolved in acetonitrile solvent 4 The EDLC cells of both electrolyte formulations exhibited regular and symmetric characteristics about the zero horizontal axis, indicating the non-redox or induced current characteristics of the cells.
[0120] Figure 17 shows the TBP-PF 6 Figure 1 shows cyclic voltammograms of EDLC cells with salt-containing ZX1170 and ZX1184 electrolytes. The electrolyte ZX1170 is F1S 3 1.2 M TBP-PF dissolved in MN 6 The electrolyte ZX1184 is DF1S 2 1.2 M TBP-PF dissolved in MN 6 The non-oxidation-reduction or dielectrophoretic characteristics can also be observed from the EDLC cells of both electrolyte ZX1170 and ZX1184 formulations.
[0121] 1ND1N synthesis: Scheme 16 shows a synthesis scheme of 1ND1N. 1ND1N can be synthesized by the synthesis of sodium (Na), calcium oxide (CaO), or calcium hydride (CaH 2 ) and cannot be dried chemically. [ka]
[0122] Electrochemical stability of 1ND1N: From the molecular orbital diagrams (not shown) for 1ND1N and 1ND1, it can be seen that the energy difference between the highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) of 1ND1N is 7.88 eV (LUMO=0.21 eV, HOMO=-7.88 eV), whereas that of 1ND1 is 8.36 eV (LUMO=1.63 eV, HOMO=-6.73 eV). 1ND1N has excellent oxidation stability, but is less resistant to reduction than 1ND1.
[0123] Figure 18 shows the LiPF of 1ND1N+1M. 6 or the oxidation stability of 1M LiTFSI at current density (mA / cm 2 ) vs. Voltage (V vs. Li / Li + The oxidation stability was measured at room temperature using a Pt working electrode, a Li counter electrode, and a Li / Li + The test was performed with a reference electrode of 100 μm and a sweep rate of 10 mV / s.
[0124] Figure 19 shows the LiPF of 1ND1N+1M. 6 or the reduction stability of 1M LiTFSI at current density (mA / cm 2 ) vs. Voltage (V vs. Li / Li + The reduction stability was measured at room temperature using a Pt working electrode, a Li counter electrode, and a Li / Li + A reference electrode and a sweep rate of 10 mV / s were tested. Two separate scans for each electrolyte are shown.
[0125] 20A and 20B show 1ND1N and 1M LiPF 6 or current density (mA / cm) when cycling from 0 to 6 V and 6 to 0 V with 1 M LiTFSI 2 ) vs. Voltage (V vs. Li / Li + ) is shown. Figure 20A shows the first cycle. Figure 20B shows the second cycle.
[0126] 21A and 21B are diagrams showing the F1S 3 MN or 1ND1N+1M LiPF 6 The oxidation stability of 2 ) vs. Voltage (V vs. Li / Li +The oxidation stability was measured at room temperature using a Pt working electrode, a Li counter electrode, and a Li / Li + The test was performed with a reference electrode of 100 μm and a sweep rate of 10 mV / s. Figure 21B shows a detailed view of the same data as in Figure 21A. 3 MN-LiPF 6 The electrolyte is 1mA / cm at 7.3V. 2 and 1ND1N-LiPF 6 The electrolyte is 1mA / cm at 7.2V. 2 The current density was
[0127] 22A and 22B are diagrams showing the F1S 3 The oxidation stability of MN or 1ND1N+1M LiTFSI was measured with a current density (mA / cm 2 ) vs. Voltage (V vs. Li / Li + The oxidation stability was measured at room temperature using a Pt working electrode, a Li counter electrode, and a Li / Li + The test was performed with a reference electrode of 1000 and a sweep rate of 10 mv / s. Figure 22B shows a detailed view of the same data as in Figure 22A. 3 The MN-LiTFSI electrolyte is 1 mA / cm at 6.2 V. 2 and the 1ND1N-LiTFSI electrolyte has a current density of 1mA / cm at 6.5V. 2 The current density was
[0128] Thermal stability of 1ND1N Figure 23 shows the thermal stability of pure 1ND1N. 1ND1N was exposed to temperatures from 30 to 189°C and analyzed for decomposition products by mass spectrometry. 1ND1N showed no liquid or gas phase decomposition products up to 189°C. 1 1 H NMR showed approximately 5% decomposition.
[0129] Figure 24 is 1ND1N+LiPF 6 The thermal stability of 1ND1N-LiPF 6 The electrolytes were exposed to temperatures between 30 and 150 °C and analyzed for decomposition products by mass spectrometry. The temperatures at which prominent peaks were observed are annotated. 1ND1N showed gas phase decomposition at ≥70 °C, but vigorous reaction was not observed up to 150 °C. Me 2 SiF 2Peaks at 81 m / z (96 g / mol) and 52 / 53 m / z, believed to be acrylonitrile (53 g / mol), appeared at temperatures between 125 and 150° C. No 1,4-dioxane gas was observed at 150° C. 1 H NMR analysis revealed that 50.6% of 1ND1N remained at 125 °C and 58% remained at 150 °C. At 125 °C, 39.7% of the fluorinated product F1NM1N (2.3% in the unheated sample) and 1.6% Me 2 SiF 2 At 150°C, the presence of 41% fluorinated product F1NM1N (2.3% in the unheated sample), 1.7% Me 2 SiF 2 The presence of 5.0% hydrolysis (5.5% in the unheated sample) and 5.0% hydrolysis (0% in the unheated sample) was observed.
[0130] 1ND1N-LiPF 6 In order to identify the peaks observed at m / z 52 / 53 when heated at 125-150°C, heated 1ND1N-LiPF 6 The mass spectral profile for was compared to that of the National Institute of Standards and Technology (NIST) standards for 2-propenenitrile and hydrogen cyanide. Figure 25A is a detailed view of the mass spectral profile from 24-30 m / z of Figure 24. Figure 25B is a detailed view of the mass spectral profile from 49-55 m / z of Figure 24. The temperatures at which prominent peaks were found in Figures 25A and 25B are annotated. The peaks at 51, 52, and 53 m / z in Figure 25B indicate the possible presence of acrylonitrile. The presence of HCN cannot be definitively confirmed or denied by the presence of peaks at 26 and 27 m / z in the NIST spectrum. The spectrum in Figure 25A shows a greater peak intensity at 26 m / z than at 27 m / z, which supports the presence of acrylonitrile. However, the magnitude of the peak at 27 m / z is greater than would be expected for acrylonitrile alone.
[0131] Figure 26 shows the thermal stability of 1ND1N+LiTFSI, vinylene carbonate (VC) and lithium bis(oxalato)borate (LiBOB). 1ND1N-LiTFSI-VC-LiBOB was exposed to temperatures from 30 to 185°C and analyzed for decomposition products by mass spectrometry. 1ND1N-LiTFSI-VC-LiBOB showed no gas phase decomposition products up to 185°C. 1 1 H NMR showed an increase in hydrolysis from 3% (in the unheated sample) to 18.7% (after heating), which is likely due to a delay before performing the NMR analysis.
[0132] Figure 27 is 1ND1N+LiBF 4 The thermal stability of 1ND1N-LiBF 4 was exposed to temperatures between 30 and 125°C and analyzed for decomposition products by mass spectrometry. The temperatures at which prominent peaks were observed are annotated. Gas phase products were generated at ≥30°C. As expected, Me 2 SiF 2 (81 m / z) (96 g / mol) was observed. No acrylonitrile was observed. 1 1 H NMR showed 3.7% hydrolysis and 34.2% fluorinated products (3 sets of peaks). 19 F NMR showed that all F in the system was bonded to Si. 4 There was not enough F to degrade 1ND1N (approximately 5M 1ND1N vs. 4M F).
[0133] Mass spectrometry revealed that heated 1ND1N-LiBF 4 No acrylonitrile was observed in the sample, but was present in the unheated control (70 ppm). This is because 1ND1N is LiBF 4 indicates that it is not stable at room temperature. NMR analysis revealed that heating had little effect on increasing decomposition, as shown in the table below.
[0134] [Table 3]
[0135] 1ND1N performance in cells: Figure 28 shows the discharge capacity at various C-rates for cells containing various electrolytes. The electrolyte solvents were (1) 1ND1N, (2) 1ND1N + 20% ethylene carbonate (EC) co-solvent (1ND1N_EC), and (3) 1ND2 + 20% EC co-solvent (1ND2_EC). All formulations contained an SEI-forming additive and 1M LiPF 6 Salt was also included. 20% EC co-solvent improved the performance of 1ND1N, as shown in Figure 28. With 20% EC co-solvent, 1ND1N showed decreased performance compared to 1ND2 at all C-rates.
[0136] Figure 29 shows the discharge capacity of cells containing various other electrolyte solvents. The electrolyte solvents are: (1) 1ND1N + 20% EC co-solvent, 1M LiPF 6 and SEI forming additive (1ND1N-EC-LiPF 6 29 as 1ND1N_EC), (2) 1ND1N + 20% EC cosolvent, 1M LiTFSI and SEI forming additive (1ND1N-EC-LiTFSI, shown in FIG. 29 as 1ND1N_T), and (3) 1ND2 + 20% EC cosolvent, 1M LiPF 6 and SEI forming additive (1ND2-EC-LiPF 6 (shown as CP597-07 in FIG. 29). 1ND1N-EC-LiPF 6 The combination of 1ND1N-EC-LiTFSI and 1ND2-EC-LiPF 6 showed performance comparable to that of the combination of
[0137] 30A and 30B are respectively 1ND1N-LiPF 630A shows the discharge capacity at various C-rates of cells containing 1ND1N-LiTFSI-based electrolyte or 1ND1N-LiTFSI-based electrolyte. For each experiment, a CR2032 coin cell with a Saft America (Cockeysville, MD) NCA cathode, graphite anode, and 2500 separator from Celgard, LLC (Charlotte, NC) was used. The cells were charged to 4.1 V at C / 5, C / 2, 1C, or 2C rates using a constant current / constant voltage (CCCV) charging method. The cells were discharged to 3.0 V at a constant current and at the same rate as when they were charged. In FIG. 30A, 1ND1N-LiPF 6 The electrolyte solution is 1M LiPF 6 In FIG. 30B, the 1ND1N-LiTFSI based electrolyte solution contained 1M LiTFSI and 1ND1N, batch (ZT781-01), and was charged / discharged at 30° C., 55° C., or 70° C. As shown in FIGS. 30A and 38B, the 1ND1N-LiTFSI based electrolyte contained 1ND1N-LiPF 6 The system electrolyte showed better rate capability.
[0138] Physical properties of OS solvents and electrolyte solutions: Table 1 above shows the properties of selected organosilicon (OS) compounds (1S 3 MN, F1S 3 MN, F1S 3 cMN, DF1S 3 MN, DF1S 2 MN and F1S 3 Table 2 shows the physical properties of pure 1ND2, 1ND1, 1ND1N F1S as an electrolyte solution and as a pure solvent. 3 MN, DPF1S 3 MN, F1S 3 MC, F1S 3 ME, F1S 3 MA, F1S 3 MS, 1NMS, F1S 3 M2 and F1S 3cThe physical properties of MN as well as various electrolyte compositions containing them are shown. In both tables, conductivity has units of mS / cm, viscosity has units of cP, and flash points are in degrees Celsius.
[0139] 1ND1N, 1ND1N, DF1S 2 MN, DF1S 3 MN, F1S 3 cMN and 1S 3 CDCl for MN 3 Protons in ( 1 H) NMR spectra are shown in Figures 31 to 36, respectively. For selected compounds containing fluorine atoms, 19 F-NMR data for CDCl 3 and DMSO-d 6 The results are summarized below:
[0140] CDCl 3 In 19 F-NMR F1S 3 MN -162.3ppm, 1 J( 19 F, 29 Si)=280Hz Iso F1S 3 MN -166.6 ppm, 1 J( 19 F, 29 Si)=284Hz DF1S 3 MN -135.3ppm, 1 J( 19 F, 29 Si)=296Hz TF1S 3 MN -136.8ppm, 1 J( 19 F, 29 Si)=280Hz DF1S 2 MN -135.2ppm, 1 J( 19 F, 29 Si)=296Hz
[0141] DMSO-d 6 In 19 F-NMR F1S 3 MN -159.2ppm, 1 J( 19 F, 29 Si)=279Hz
[0142] Thermal stability of OS electrolyte solutions: Figures 37 and 38 show the F1S 3 MC, F1S 3 cMN, 1S 3 DN DF1S 2 MN, TF1S 2 MN and TF1S 3 MN+1M LiPF 6 Each electrolyte was exposed to temperatures from 30 to 175°C (60 min for each step) and analyzed for gas and liquid decomposition products by electron impact mass spectrometry (EI-MS) and nuclear magnetic resonance spectroscopy (NMR), respectively. No significant gas and / or liquid phase decomposition was observed up to 175°C.
[0143] Conclusion: F1S 3 Both MN and 1ND1N are suitable for use as electrolyte solvents in lithium-ion batteries. 3 MN and DF1S 2 MN has been demonstrated to function as an electrolyte solvent in EDLC devices. 3 MN exhibited extremely high thermal stability ( 1 1 H NMR) are shown. 3 MN has the highest thermal stability among the OS compared to LiPF 6 (175°C) and no decomposition was observed. 3 MN reacts with the gas-phase product as a pure solvent, LiBF 4 and LiTFSI. These gas-phase products contain low levels of F1S 3 This can be attributed to the evaporation of MN. F1S 3 MN is F1S 3It shows higher voltage stability than M2 (wider window and higher oxidation potential). F1S 3 MN provides the same performance as EPA6 up to a rate of 4C. LiBOB's F1S 3 The solubility in MN (<0.03M) is limited without a co-solvent, but the solubility of LiBOB is improved (>0.1M) with the use of a co-solvent (i.e., 20% EC). 3 The decomposition product of MN is Me 2 SiF 2 and MeSiF 3 and both are gases.
[0144] 1ND1N does not show any gas-phase decomposition up to 185-190°C either as a pure solvent or in combination with LiTFSI electrolyte. The combination of 1ND1N with LiTFSI electrolyte is promising up to 70°C and above. 1ND1N+LiPF 6 1ND1 or 1ND2+LiPF 6 It is more thermally stable. Above 125 °C it forms acrylonitrile. Like the other non-spacer compounds, 1ND1N forms LiBF at room temperature. 4 However, there is not enough F to completely decompose 1ND1N to produce acrylonitrile. The rate performance of 1ND1N is slightly lower than that of 1ND2.
[0145] F1S 3 ME, DPF1S 3 MN and F1S 3 All MCs are suitable for use as electrolyte solvents in lithium-ion batteries. 3 MC, F1S 3c M.N., 1S. 3 DN, DF1S 2 MN, TF1S 2 MN and TF1S 3 MN is LiPF 6 It exhibits thermal stability (up to 175°C) and no decomposition is observed.
[0146] Yet another aspect of the present invention may be as follows. [1] [ka] is selected from the group consisting of "a" is an integer from 1 to 4, and "b" is an integer from 0 to (3×a); "Z" does not exist when "b" = 0, and "R" and [ka] is selected from the group consisting of Each "R" is independently halogen, C 1-6 Linear or branched alkyl, alkenyl or alkynyl and C 1-6 selected from the group consisting of linear or branched halo-alkyl, halo-alkenyl, or halo-alkynyl; Each "Sp" in formulas I and II is independently 1-15 Linear or branched alkylenyl and C 1-15 linear or branched halo-alkylenyl; A compound of formula I, wherein each "Y" is independently selected from the group consisting of organic polar groups. [2] Each "Y" is independently: [ka] and the curved bond is selected from the group consisting of C 2-6 The compound according to [1] above, which shows an alkylene bridge portion. [3] Each "Y" is independently: [ka] The compound according to [2] above, wherein the organic polar group is selected from the group consisting of: [4] Each "R" is independently fluorine or C 1-6 selected from the group consisting of linear or branched fluoro-alkyl, fluoro-alkenyl or fluoro-alkynyl; Each "Sp" in formulas I and II is independently 1-15 The compound according to claim 3, wherein the alkyl group is selected from the group consisting of linear or branched fluoro-alkylenyl. [5] The compound according to any one of the above [1] to [4], wherein "a" is 1 and "b" is 0 to 3. [6] The compound according to [5] above, wherein "b" is 1 and "Z" is "-R". [7] At least one "R" is fluorine and each "Sp" is independently C 1-6 Linear alkylene and C 1-6 The compound according to claim 5, wherein the compound is selected from the group consisting of linear fluoro-alkylenes. [8] The compound according to any one of the above [1] to [4], wherein "a" is 2 and "b" is 0 to 6. [9] The compound according to [7] above, wherein "b" is 1 and "Z" is "R".
[10] At least one "R" is fluorine and each "Sp" is independently C 1-6 The compound according to claim 7, wherein the alkylene is selected from the group consisting of straight chain alkylene.
[11] The compound according to any one of the above [1] to [4], wherein "a" is 3 and "b" is 0 to 9.
[12] The compound according to
[11] above, wherein "b" is 1 and "Z" is "R".
[13] At least one "R" is fluorine and each "Sp" is independently C 1-6 The compound according to claim 11, wherein the alkylene is selected from the group consisting of straight chain alkylene.
[14] The compound according to any one of the above [1] to [4], wherein "a" is 4 and "b" is 0 to 12.
[15] The compound according to
[14] above, wherein "b" is 1 and "Z" is "R".
[16] At least one "R" is fluorine and each "Sp" is independently C 1-6 The compound according to claim 14, wherein the alkylene is selected from the group consisting of straight chain alkylene.
[17] The compound according to any one of the above [1] to [4], wherein at least one "R" is fluorine.
[18] An electrolyte composition comprising the compound according to any one of [1] to [4] above in combination with a salt.
[19] The electrolyte composition according to
[18] above, wherein the salt is a lithium-containing salt.
[20] An electrochemical device comprising the electrolyte composition according to
[18] . Yet another aspect of the present invention may be as follows. [1'] [ka] and a lithium-containing salt, "a" is 1 and "b" is an integer from 0 to 1, "Z" does not exist when "b" = 0, and "R" and [ka] is selected from the group consisting of Each "R" is independently halogen, C 1-6 Linear or branched alkyl, alkenyl or alkynyl and C 1-6 selected from the group consisting of linear or branched halo-alkyl, halo-alkenyl, or halo-alkynyl, wherein at least one "R" is fluorine; Each "Sp" in formulas I and II is independently 1-15 linear or branched alkylenyl; Each "Y" in formula I is independently [ka] The electrolyte composition comprises an organic polar group selected from the group consisting of: [2'] Each "R" is independently fluorine, or C 1-6 The electrolyte composition according to the above [1'], wherein the fluoro-alkyl group is selected from the group consisting of linear or branched fluoro-alkyl, fluoro-alkenyl, or fluoro-alkynyl. [3'] The electrolyte composition according to [1'] or [2'], wherein "b" is 1 and "Z" is "-R". [4'] Each "Sp" is independently C 1-6The electrolyte composition according to any one of the above [1'] to [3'], wherein the alkylene group is selected from the group consisting of linear alkylenes. [5'] The lithium-containing salt is LiClO 4 , LiBF 4 , LiAsF 6 , LiPF 6 , LiCF 3 SO 3 , Li(CF 3 SO 2 ) 2 N, Li(CF 3 SO 2 ) 3 C, LiN(SO 2 C 2 F 5 ) 2 The electrolyte composition according to any one of the above [1'] to [4'], wherein the lithium bis(chelate)borate is selected from the group consisting of lithium alkylfluorophosphate, lithium alkylfluorophosphate, and lithium bis(chelate)borate. [6'] An electrochemical device comprising the electrolyte composition according to any one of [1'] to [5'] above.
Claims
【Request 1】 【Chemistry 1】 is selected from the group consisting of "a" is an integer from 1 to 4, and "b" is an integer from 0 to (3×a); "Z" does not exist when "b"=0, and "R" and 【Chemistry 2】 is selected from the group consisting of Each "R" is independently halogen, C 1-6 Linear or branched alkyl, alkenyl or alkynyl and C 1-6 selected from the group consisting of linear or branched halo-alkyl, halo-alkenyl, or halo-alkynyl; Each "Sp" in formula I and II is independently C 1-15 Linear or branched alkylenyl and C 1-15 linear or branched halo-alkylenyl; A compound of formula I, wherein each "Y" is independently selected from the group consisting of organic polar groups.
2. Each "Y" is independently 【Chemistry 3】 and the curved bond is selected from the group consisting of C 2-6 The compound of claim 1 , exhibiting an alkylene bridging moiety.
3. Each "Y" is independently 【Chemistry 4】 3. The compound of claim 2, wherein the organic polar group is selected from the group consisting of:
4. Each "R" is independently fluorine, and C 1-6 selected from the group consisting of linear or branched fluoro-alkyl, fluoro-alkenyl or fluoro-alkynyl; Each "Sp" in formula I and II is independently C 1-15 The compound of claim 3, selected from the group consisting of linear or branched fluoro-alkylenyl.
5. The compound according to any one of claims 1 to 4, wherein "a" is 1 and "b" is 0 to 3.
6. The compound of claim 5, wherein "b" is 1 and "Z" is -R.
7. At least one "R" is fluorine and each "Sp" is independently C 1-6 Linear alkylene and C 1-6 The compound of claim 5, selected from the group consisting of linear fluoro-alkylenes.
8. The compound according to any one of claims 1 to 4, wherein "a" is 2 and "b" is 0 to 6.
9. 8. The compound of claim 7, wherein "b" is 1 and "Z" is "R".
10. At least one "R" is fluorine and each "Sp" is independently C 1-6 8. The compound of claim 7, wherein the alkyl group is selected from the group consisting of straight chain alkylene.
11. The compound according to any one of claims 1 to 4, wherein "a" is 3 and "b" is 0 to 9.
12. 12. The compound of claim 11, wherein "b" is 1 and "Z" is "R".
13. At least one "R" is fluorine and each "Sp" is independently C 1-6 12. The compound of claim 11, wherein the alkyl group is selected from the group consisting of straight chain alkylene.
14. The compound according to any one of claims 1 to 4, wherein "a" is 4 and "b" is 0 to 12.
15. 15. The compound of claim 14, wherein "b" is 1 and "Z" is "R".
16. At least one "R" is fluorine and each "Sp" is independently C 1-6 15. The compound of claim 14, wherein the alkyl group is selected from the group consisting of straight chain alkylenes.
17. The compound according to any one of claims 1 to 4, wherein at least one "R" is fluorine.
18. An electrolyte composition comprising a compound according to any one of claims 1 to 4 in combination with a salt.
19. 20. The electrolyte composition of claim 18, wherein the salt is a lithium-containing salt.
20. 20. An electrochemical device comprising the electrolyte composition of claim 18.